A case of Leaking Abdominal Aortic Aneurysm - Haque, Rashedul; Faruq, Mohammad Omar; Sultana, Amina; Rahman, Mir Atiqur; Shamarukh, Karishma; Hasan, S M Razibul (Bangladesh Critical Care Journal, 2019)
Abstract not available Bangladesh Crit Care J September 2019; 7(2): 116-117